2014
DOI: 10.1002/2014ja020125
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of relativistic outer belt electrons during an extended quiescent period

Abstract: To effectively study loss due to hiss‐driven precipitation of relativistic electrons in the outer radiation belt, it is useful to isolate this loss by studying a time of relatively quiet geomagnetic activity. We present a case of initial enhancement and slow, steady decay of 700 keV–2 MeV electron populations in the outer radiation belt during an extended quiescent period from ∼15 December 2012 to 13 January 2013. We incorporate particle measurements from a constellation of satellites, including the Colorado S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
3
38
0
1
Order By: Relevance
“…Evidence for such a gradient in localized regions of the magnetosphere have been presented previously (e.g., Hilmer et al, 2000;McAdams et al, 2001;Selesnick & Blake, 2000). However, if a local maximum in the PSD versus L-shell distribution exists (e.g., Boyd et al, 2014;Jaynes et al, 2014;Schiller et al, 2014;Taylor et al, 2004), then the gradient tailward of that peak would be negative (Sergeev et al, 1992), which would result in a PSD decrease at a given L-shell during an earthward injection (Figure 4b). However, if a local maximum in the PSD versus L-shell distribution exists (e.g., Boyd et al, 2014;Jaynes et al, 2014;Schiller et al, 2014;Taylor et al, 2004), then the gradient tailward of that peak would be negative (Sergeev et al, 1992), which would result in a PSD decrease at a given L-shell during an earthward injection (Figure 4b).…”
Section: Determining Potential Source Mechanismsmentioning
confidence: 51%
“…Evidence for such a gradient in localized regions of the magnetosphere have been presented previously (e.g., Hilmer et al, 2000;McAdams et al, 2001;Selesnick & Blake, 2000). However, if a local maximum in the PSD versus L-shell distribution exists (e.g., Boyd et al, 2014;Jaynes et al, 2014;Schiller et al, 2014;Taylor et al, 2004), then the gradient tailward of that peak would be negative (Sergeev et al, 1992), which would result in a PSD decrease at a given L-shell during an earthward injection (Figure 4b). However, if a local maximum in the PSD versus L-shell distribution exists (e.g., Boyd et al, 2014;Jaynes et al, 2014;Schiller et al, 2014;Taylor et al, 2004), then the gradient tailward of that peak would be negative (Sergeev et al, 1992), which would result in a PSD decrease at a given L-shell during an earthward injection (Figure 4b).…”
Section: Determining Potential Source Mechanismsmentioning
confidence: 51%
“…Moreover, the activity of plasmaspheric hiss is limited mostly inside the plasmapause , which was compressed up to L = 3 during both of the events. Even if the plasmapause were located at higher L shells, hiss-driven electron precipitation has a timescale from ≈ 1 day to tens of days depending on energy Thorne et al, 2013;Jaynes et al, 2014) and not a few hours. In addition, this depletion is consistent with the results of Loto'aniu et al (2010), who showed that non-adiabatic losses on 25 June 2008 event occurred over a timescale of 1-4 h.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Usanova et al (2014) combined electron precipitation observations and simulations to show that EMIC waves were able to affect the low pitch angle electrons in the outer belt, but not the core of the electron distribution during the 11 October 2012 event. In addition, Jaynes et al (2014) showed that in the absence of additional energization, plasmaspheric hiss was responsible for continuous losses of electrons inside the plasmasphere during the time period 22 December 2012 through 13 January 2013. showed that the majority of nonadiabatic losses of outer radiation belt electrons with energies above 300 keV during the main phase of the 6 January 2011 geomagnetic storm were not lost to the atmosphere but to Earth's magnetopause through magnetopause shadowing and subsequent rapid outward radial transport. Even in the case of limited compression of the magnetosphere, Ni et al (2011) showed that there is a clear correlation between electron PSD dropouts and the solar wind pressure pulse, owing to a combination of magnetopause shadowing and outward radial diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Figures a–e). We will show that the widely extended plasmasphere ( L > 5) favors long lasting hiss losses in the outer belt (see also [ Jaynes et al , ]). The electron pitch angle scattering that we will compute in section 3 and 4 is a major contributor to the structure of the belts we observe and compute (cf.…”
Section: Wave and Plasma Modelsmentioning
confidence: 92%